Knowing how to live with rheumathoid arthritis or ankylosing spondilytis during pregnancy - Araújo Correia, João (2009)
Rheumathoid arthritis and ankylosing spondilytis are diseases that strike young women that eventually demonstrate the desire of getting pregnant. The doctor must be prepared to answer all questions, pointing out the advantages of planned pregnancy. The main goal, by achieving the strong collaboration between the obstetrician and the internist or rheumatologist, is to maintain the illness inactive, with the safest drugs for the mother and the fetus. Nothing can stop a woman with RA or AS from being a mother. In general, one can say pregnancy is a period of immunologic tolerance, being even possible to wait for these diseases to get better.